2007
DOI: 10.1111/j.1740-8784.2007.00080.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Social Capital: Networks of Entrepreneurs and Venture Capitalists in China and Russia

Abstract: I compare networks of entrepreneurs and venture capitalists in China and Russia by examining professional social networks of software entrepreneurs and private equity investors from the perspectives of institutional theory and culture paradigm. In the empirical study, I draw on survey data from Beijing and Moscow based on interviews of 159 software entrepreneurs and 124 venture capital decisions. I found that professional networks of the Chinese software entrepreneurs are smaller, denser and more homogeneous i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 54 publications
(94 reference statements)
2
71
0
1
Order By: Relevance
“…The nature of business networks in Vietnam is still mainly political and somewhat compulsory for established incumbent firms in capital-intensive or mature industries. Nevertheless, as shown by McMillan and Woodruff (1999) for Vietnam and other authors for Russia (Batjargal, 2007), Eastern Europe (Paldam and Svendsen, 2000), and China (Koch, 2005), evidences of social capital benefits from business network participation are being observed also in transitional economies. Therefore, future policy action should encourage the establishment of genuinely business-oriented networks (rather than politically based) to support directly entrepreneurs, especially small-sized ones, in both their daily operations and long-term strategic management.…”
Section: Discussion and Suggestions For Policy Actionsmentioning
confidence: 93%
“…The nature of business networks in Vietnam is still mainly political and somewhat compulsory for established incumbent firms in capital-intensive or mature industries. Nevertheless, as shown by McMillan and Woodruff (1999) for Vietnam and other authors for Russia (Batjargal, 2007), Eastern Europe (Paldam and Svendsen, 2000), and China (Koch, 2005), evidences of social capital benefits from business network participation are being observed also in transitional economies. Therefore, future policy action should encourage the establishment of genuinely business-oriented networks (rather than politically based) to support directly entrepreneurs, especially small-sized ones, in both their daily operations and long-term strategic management.…”
Section: Discussion and Suggestions For Policy Actionsmentioning
confidence: 93%
“…Following the collapse of the Soviet Union, and while Russia continues to transition into a more market-based economy, the importance of connections with government officials has remained relatively consistent. It has been argued that in this emerging economy it is still very much the case that knowing 'the right people' is vital to the success of entrepreneurial behaviour (Batjargal, 2005). Entrepreneurs without ties to state bureaucrats face significant barriers to entry and a generally more hostile business operating environment (Guseva, 2007).…”
Section: Relationships With Government Officialsmentioning
confidence: 99%
“…In line with the findings regarding the role of networks in Russian society, the studies of networks in the Russian economy have confirmed their role across a variety of economic contexts such as labor markets (Clarke and Kabalina 2000;Yakubovich and Kozina 2000;Yakubovich 2005), banking (Guseva and Rona-Tass 2001) and entrepreneurship and firm performance (Aidis et al 2008;Shmulyar Gréen 2009;Batjargal 2003Batjargal , 2005aBatjargal , b, 2007Rogers 2006). 9 Because of the wide range of study areas, different theoretical backgrounds, a range of methods mostly not designed for network research and often-metaphorical notions of networks, this literature does not produce coherent or accumulating results.…”
Section: The Role Of Social Network In the Soviet And Russian Econommentioning
confidence: 53%